A Sustainable Multi-Stakeholder Approach for Connecting the ‘Next Billion’ Telecommunication Subscribers at the Bottom of the Pyramid – Cases from Asia - Siow, Victor Chee Yeang (2009)
The mobile telecommunications business is becoming increasingly hyper competitive as market saturation is almost at the maximum, especially in urban areas and developed countries. However, mobile communications services have not reached to about half the world’s population. These people predominantly reside in rural areas and emerging markets and have very low-income. This segment can be termed as the ‘Bottom of the Pyramid’ (BOP) market. So why haven’t mobile telecommunication companies seized this opportunity at the BOP? There are two ways of looking at the people bottom of the economic pyramid. Either you view them as people who are unable to afford mobile communications due to poverty or challenge the assumption that these people are willing to spend on services if they are given the right support and opportunity. So the question to managers is do we categorize this group of people as a market segment that is unable to afford our products and services? Or is our strategy and operations structured in a way that makes these products and services priced out of reach or irrelevant to this segments daily needs? Corporate Social Responsibility (CSR) has also gained a lot of hype in recent years. Many corporations now see the need to have some sort of CSR program. Questions are being raised about the motives of some CSR programs. Is it just a ‘green-washing’ (public relations) exercise or does it really help a firm to improve its competitive context and grow into a sustainable business? This research paper sets out to explore some of these overarching issues. Five companies were chosen and developed into best practices case studies to show how these companies are tackling these issues. The findings will be methodologically analyzed and compared with theoretical literature. Finally, recommendations will be made, addressed to telecommunication companies that are interested in penetrating and growing their business in BOP-type markets.